Partial root-zone drying combined with nitrogen treatments mitigates drought responses in rice - Zhao, Minhua; Gao, Zhihong; Kuang, Chunyi; Chen, Xiaoyuan (Frontiers in Plant Science, 2024)
Drought is a major stress affecting rice yields. Combining partial root-zone drying (PRD) and different nitrogen fertilizers reduces the damage caused by water stress in rice. However, the underlying molecular mechanisms remain unclear. In this study, we combined treatments with PRD and ammonia:nitrate nitrogen at 0:100 (PRD0:100) and 50:50 (PRD50:50) ratios or PEG and nitrate nitrogen at 0:100 (PEG0:100) ratios in rice. Physiological, transcriptomic, and metabolomic analyses were performed on rice leaves to identify key genes involved in water stress tolerance under different nitrogen forms and PRD pretreatments. Our results indicated that, in contrast to PRD0:100, PRD50:50 elevated the superoxide dismutase activity in leaves to accelerate the scavenging of ROS accumulated by osmotic stress, attenuated the degree of membrane lipid peroxidation, stabilized photosynthesis, and elevated the relative water content of leaves to alleviate the drought-induced osmotic stress. Moreover, the alleviation ability was better under PRD50:50 treatment than under PRD0:100. Integrated transcriptome and metabolome analyses of PRD0:100 vs PRD50:50 revealed that the differences in PRD involvement in water stress tolerance under different nitrogen pretreatments were mainly in photosynthesis, oxidative stress, nitrogen metabolism process, phytohormone signaling, and biosynthesis of other secondary metabolites. Some key genes may play an important role in these pathways, including OsGRX4, OsNDPK2, OsGS1;1, OsNR1.2, OsSUS7, and YGL8. Thus, the osmotic stress tolerance mediated by PRD and nitrogen cotreatment is influenced by different nitrogen forms. Our results provide new insights into osmotic stress tolerance mediated by PRD and nitrogen cotreatment, demonstrate the essential role of nitrogen morphology in PRD-induced molecular regulation, and identify genes that contribute to further improving stress tolerance in rice.